1978
DOI: 10.1037/0033-2909.85.5.1030
|View full text |Cite
|
Sign up to set email alerts
|

Just world research and the attribution process: Looking back and ahead.

Abstract: The just world hypothesis states that people have a need to believe that their environment is a just and orderly place where people usually get what they deserve. This article reviews the experimental research that has been generated by the just world hypothesis. In light of the existing empirical findings, an elaboration of the initial hypothesis is offered, as are suggestions for potential avenues of future research. Finally, recurrent conceptual misinterpretations and methodological errors found in the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

29
911
6
49

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,304 publications
(1,020 citation statements)
references
References 60 publications
29
911
6
49
Order By: Relevance
“…Research on the belief in a just world has shown that when people's belief in a just world is threatened by an innocent victim, they often react by blaming the victim or derogating his or her character if they cannot rectify the situation (see Hafer & Begue, 2005;Lerner & Miller, 1978;Lerner & Simmons, 1966). If the victim deserves his or her fate, no injustice has occurred and the worldview is preserved.…”
Section: Cultural Worldviews and Status Ideologiesmentioning
confidence: 99%
“…Research on the belief in a just world has shown that when people's belief in a just world is threatened by an innocent victim, they often react by blaming the victim or derogating his or her character if they cannot rectify the situation (see Hafer & Begue, 2005;Lerner & Miller, 1978;Lerner & Simmons, 1966). If the victim deserves his or her fate, no injustice has occurred and the worldview is preserved.…”
Section: Cultural Worldviews and Status Ideologiesmentioning
confidence: 99%
“…popularity over the past 40 years (for reviews see Furnham, 2003;Furnham and Procter, 1989;Hafer and Bègue, 2005;Lerner and Miller, 1978). A great deal of this research has focused on the implications of a need to believe in a just world for reactions to various types of victims as well as on the correlates of individual differences in the strength of people's belief in a just world.…”
mentioning
confidence: 99%
“…In the same vein, the status degradation and the disempowerment imposed by the legal system to the offender is a punishment that serves a just deserts perspective (Darley & Pittman, 2003). That is, it is not only a legal issue that maintains social order, but also responds to a psychological need for citizens who live in society, which need to know that their environment is a safe and just place where people obtain what they deserve (Lerner, 1980;Lerner & Miller, 1978).…”
mentioning
confidence: 99%